REVIEW OF AMIL ZAKAT IN PERSPECTIVE CONTEMPORARY ISLAMIC LAW - Hasanah, Uswah; Naimi, Nadlrah (Proceeding International Seminar of Islamic Studies, 2024)
Zakat is one of the five pillars of Islam. One of the people entitled to receive zakat is {mustahiqqin). is "amyl". .In this case, sometimes several questions arise from this amil, especially about who can be called amil zakat, what are the criteria for this amil and contemporary issues at this time. The issue above is certainly very interesting to discuss, especially if it is related to the conditions and developments in the implementation of zakat obligations by muzakki today, especially zakat fitrah who are more likely to use amil services. In general, people pay their zakat fitrah and there is also zakat mal through the zakat amil committee. Can the people or committees of the zakat amil be positioned as amil as intended by the Koran verse 60 of the at-Taubah letter? Study of fiqh interpretation on this matter is really necessary. This research will examine how amil zakat is viewed in contemporary fiqh. The research method is qualitative, namely originating from contemporary fiqh law regarding the implementation of zakat. The research results show that Amil zakat in the legal interpretation of the mufassir has 2 criteria. 1). Activities to manage zakat assets, both as daily administrators and as members of sections in the management of zakat amil institutions. 2). Appointed by the government through a confirmation procedure.